The Role of Hedonic Motivation As The Mediator In The Effect of Social Media Endorsement Short Video Toward Impulsive Repurchase Intention on Generation Z - Nurasti, Anandita; Sobari, Nurdin (UI Scholars Hub, 2023)
Manuscript Type: Research Paper Research Aims: To analyze how demand, convenience, interactivity, and playfulness in short videos influence perceived enjoyment, which in turn affects hedonic motivation and impulsive repurchase intentions, both directly and indirectly.Design/Methodology/Approach: This study used quantitative research with 278 respondents, analyzed using structural equation modeling (SEM). Research Findings: Demand, convenience, and playfulness significantly enhance perceived enjoyment, while interactivity does not. Perceived enjoyment positively influences hedonic motivation, which partially mediates its effect on impulsive repurchase intention.Theoritical Contribution/Originality: This study reveals that stimuli in short video endorsements, including demand, convenience, and playfulness, significantly boost perceived enjoyment and hedonic motivation in Generation Z, influencing impulsive repurchase intentions, particularly among female consumers.Practitioner/Policy Implication: Short videos fail to capture the interactions between influencers and audiences, so brands should be cautious when using them to boost consumer loyalty. For Generation Z, impulse repurchase intention is more influenced by the short video format than by hedonic motivation, highlighting the importance of playfulness. This research offers brands valuable insights for using short videos as a promotional strategy.Research Limitation/Implications: Interactivity in short videos differs from live streaming, and the specific clothing brand used is unidentifiable, raising concerns about respondents' brand recall. Additionally, the pre-test lacked confirmatory factor analysis (CFA), did not validate wording, and removed indicators without justification. Keywords: demand, convenience, interactivity, playfulness, perceived enjoyment, hedonic motivation, impulsive repurchase intention, short video, Generation Z.